Analisis Sifat Mekanik dan Penyerapan Air Komposit Polyester Berbasis Serat Alami - Kus Andrianto, Sis Nanda; Maulana, Jibril; Sentosa Riyanto, Obaja Eden; Tsamroh, Dewi Izzatus; Nur Sasongko, Muhammad Ilman; Andromeda, Tata; Simangunsong, Rahel; Fahrozy, Muhammad Micho (Politeknik Negeri Jakarta, 2025)
Natural fibers are increasingly utilized as reinforcing materials in the modern materials industry. In this study, composites comprising 15% untreated coconut fiber, pineapple leaf fiber, palm fiber, corn husk fiber, or sugar cane fiber and 85% polyester were fabricated. Water absorption was evaluated by immersing the composites for 3, 7, 14, and 21 days. The tensile strength and morphology of unsoaked composites were also assessed to determine the influence of fiber type. Water absorption increased with immersion time for all composites, although the trends varied among fiber types. The coconut fiber composite exhibited the highest water absorption rate, whereas the pineapple leaf fiber composite demonstrated the lowest. The pineapple leaf fiber composite also achieved the highest tensile strength. In contrast, composites containing coconut fiber, palm fiber, corn husk fiber, and sugar cane fiber displayed lower tensile strength, attributed to imperfect interfacial bonding between the fibers and the polyester matrix.